THE IMPACT OF FINANCIAL BALANCE INDICATORS ON THE DEBT TO EQUITY RATIO - AN APPLIED STUDY OF SEVERAL BANKS IN IRAQ - Jamal hadash Mohammed (Galaxy International Interdisciplinary Research Journal, 2024)
This study aims to evaluate the impact of financial balance on the debt to equity ratio of banks by using three main indicators: the liquidity indicator, the profitability indicator, and the solvency indicator. The debt to equity ratio was measured as a dependent variable . Four commercial banks listed on the Iraq Stock Exchange were purposively selected as the sample for this study, covering the period from 2012 to 2021. Descriptive and analytical methods were used to review and analyze the financial data available from the reports and financial statements of the concerned banks. To support the applied aspect of the study, statistical analysis and financial description software such as Excel 2016 and EViews were used .The study’s results indicated that the banks in the sample exhibited a long-term inverse effect of financial balance indicators on the debt to equity ratio. Based on these results, the study recommended utilizing surplus liquidity to achieve additional returns for the bank .